Mitigating Regulatory Risk in Telecommunications - Smith, Peter L. (World Bank, Washington, DC, 2012)
In the transition from state-owned monopolies to privately led and increasingly competitive market structures in telecommunications, poor performance of regulatory agencies limits the benefits of reform. This Note proposes measures for establishing a regulatory framework that enables better sector performance even when a full-fledged regulatory agency is lacking. These measures reduce the need for agency decisions -- for example, by prepackaging rules and accelerating competition. They enhance the credibility of regulation -- for example, by locking in principles through international agreements. And they generate maximum impact from scarce professional and financial resources by using them effectively -- such as by contracting out functions and creating multisectoral or regional agencies.